Revision of Nearctic Phthinia Winnertz (Diptera: Mycetophilidae) - Fitzgerald, Scott J.; Kerr, Peter H. (Zootaxa, 2014)
The Nearctic species of Phthinia Winnertz are revised. Eight species are recognized, of which four are newly described; P. tanypus Loew (= P. carolina Fisher n. syn., and P. catawbiensis Shaw n. syn.), P. lobata Zaitzev, P. miranda Zaitzev, P. ramificans Zaitzev, P. nepunei n. sp., P. cascadica n. sp., P. meicigama n. sp. and P. mikmaqi n. sp. A key to these species is also provided.